TANTANGAN STUDI ISLAM DI ERA MODERN DAN KEBUTUHAN METODOLOGI INTERDISIPLINER SEBAGAI PENDEKATAN ALTERNATIF - Auliya`, Hilyatul; Kurjum, Mohammad (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2025)
Islamic studies in Indonesia continue to grow alongside increasingly complex social, political, and technological changes. Yet this development presents challenges that cannot be resolved with purely normative and textual perspectives. This study identifies key issues in contemporary Islamic scholarship, critiques the limitations of traditional methods, and highlights the urgency of interdisciplinary approaches. Through a qualitative literature review, data were drawn from journals, books, and research reports. The findings indicate three major challenges: the enduring influence of Orientalism, declining interest in religious disciplines compared to general sciences, and global competition that requires stronger academic performance. Conventional approaches fall short when dealing with modern themes such as gender justice, environmental concerns, and digital transformation. As a result, integrating Islamic texts with social sciences, humanities, and scientific disciplines becomes essential. This paradigm shift has been adopted by institutions like UIN Sunan Kalijaga, UIN Jakarta, and UIN Sunan Ampel Surabaya, supported by Ministry of Religious Affairs research programs. Interdisciplinary methodologies ultimately strengthen the relevance and competitiveness of Islamic studies in addressing contemporary challenges.